The remarkable role of metal promoters on the catalytic activity of Co-Cu based nanoparticles for boosting hydrogen evolution: Ammonia borane hydrolysis - Filiz, Bilge Coskuner; Figen, Aysel Kanturk; Piskin, Sabriye (ELSEVIER, 2018)
The development of highly efficient catalysts for hydrogen evolution has a crucial significance due to adaptation for sustainable clean energy systems. This study provides potentially powerful approach for catalytic hydrogen evolution based on ammonia borane (NH3BH3) hydrolysis in presence of ternary metal nanoparticles (TMNPs). Herein, we draw up a strategy by using non-noble (Ni, Ag) and noble (Ru, Pt, Pd and Rh) metal promoters in the structure of Co-Cu nanoparticles to boost their catalytic activity for hydrogen evolution by NH3BH3 hydrolysis. Internal and external properties of TMNPs catalysts are characterized by using XRD, SEM/EDS, FTIR, XPS, XRF, ICP-OES, BET, TEM and SAED/HRTEM techniques and performed for hydrogen evolution tests. Kinetic and thermodynamic assessments, bimolecular reaction mechanism investigation and reusability-recyclability-stability performance results relieve that Rh promoted CoCu TMNPs delivers highest hydrogen evolution activity with 21.21 l H-2 g(-1) cat min(-1), 8582 mol(H2) mol(cat)(-1) h(-1) initial turnover frequency (TOF) value, and 36.50 kJ mol(-1) activation energy (E-a) by providing the release of 3 equivalent H-2 per mole of NH3BH3 even after 10th use of catalytic performance tests.
Keywords: Promoter; Nanoparticles; Co-Cu catalyst; Ammonia borane; Hydrogen; Electronic influence; ALLOY NANOPARTICLES; PALLADIUM CATALYSTS; GENERATION SYSTEM; NI; DEHYDROGENATION; CARBON; SUPPORT; RUTHENIUM(0); NANOCLUSTERS; METHANOLYSIS; Chemistry; Engineering